A novel allele, HLA‐B*15:259, was identified in a Taiwanese individual by sequence‐based typing. (20th January 2016) - Chang, C. L.; Lin, C. Y.
Abstract : A one nucleotide replacement in codon 24 of HLA‐B*15:54 results in a novel allele, HLA‐B*15:259 .